phytochemical investigations of Iraqi Abrus precatorius Linn. plant - S. Nassir, Zahra’a; J. Khadem, Enas (Iraqi Journal of Pharmaceutical Sciences, 2018)
The plant Abrus precatorius, which belong to Leguminosae (Fabaceae) family and known as Crab’s eyes, Rosary pea with characteristic red and black seeds. It was used in folk medicine in India, China and East Asian countries for treatment of various diseases. The plant was extracted by ’’ general method of extraction’’ (Harborne, 1973) using 80% aqueous ethanol as a solvent of extraction by soxhlet apparatus. Preliminary qualitative phytochemical screening were performed on the crude ethanolic extract and revealed the presence of alkaloids, flavonoids ,terpenoids and phytosterols in Iraqi Abrus precatorius plant. Three different fractions were obtained from crude extract which are fraction one (chloroform fraction), fraction two (ethyl acetate fraction), and fraction three (petroleum ether fraction) which are represent alkaloids, flavonoids and steroids respectively. The alkaloid abrine was isolated from the chloroform fraction in pure form by using preparative thin layer chromatography (PTLC) and then subjected to different physico-chemical and specteral analytical techniques to identify its chemical structure: melting point (M.P.), thin layer chromatography (TLC), high performance liquid chromatography (HPLC) , fourier transforms infrared spectra (FT-IR) and elemental microanalysis (CHNO).